Lessons learned from the Tokyo games isolation hotel experience - Olin, J. T.; Fredericson, M.; Nichol, C.; Willick, S. E.; Clemm, H. H. (British Journal of Sports Medicine, 2022)
Despite the SARS-CoV-2 pandemic, the Tokyo2020 Organizing Committee (TOGOC), IOC, International Paralympic Committee (IPC) and National Olympic and Paralympic Committees (NOC/NPCs) delivered events across 42 venues for over 15 000 athletes from over 200 countries. Athletes lived in congregate housing (Olympic and Paralympic Village) within a metropolis featuring to record SARS-CoV-2 infections and resistance to the Games.1 Across 2 months of operations, over 1 million tests were performed on athletes and staff. There were fewer than 500 confirmed positive results, the majority outside the Athlete`s Village, involving volunteers and contractors. Less than 40 positive tests were detected among athletes.2 3